2019
DOI: 10.1111/acem.13872
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Partial Thromboplastin Times in Patients With Pulmonary Embolism During the First 48 Hours of Anticoagulation With Unfractionated Heparin

Abstract: Objective The objective was to determine the proportion of patients with pulmonary embolism (PE) treated with unfractionated heparin (UFH) who achieved therapeutic activated partial thromboplastin time (aPTT) values within 48 hours of treatment. Methods Retrospective analysis of a PE response team (PERT) database was performed at a large, urban, academic teaching hospital. Inclusion criteria were adult patients with acute PE for whom the PERT was consulted and who received anticoagulation (AC) with UFH accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
0
29
1
1
Order By: Relevance
“…However, the use of dose-adjusted unfractionated heparin often fails to achieve a therapeutic effect on the activated partial-thromboplastin time within 48 hours after initiation. 22 Low-molecular-weight heparin at a weight-based dose is more biologically predictable and is associated with a lower risk of additional thrombus formation and bleeding, as well as smaller thrombi, than dose-adjusted intravenous unfractionated heparin. 23 The use of up-front direct oral anticoagulant agents (factor II and X inhibitors) is also appropriate for patients with lower-risk pulmonary embolism.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…However, the use of dose-adjusted unfractionated heparin often fails to achieve a therapeutic effect on the activated partial-thromboplastin time within 48 hours after initiation. 22 Low-molecular-weight heparin at a weight-based dose is more biologically predictable and is associated with a lower risk of additional thrombus formation and bleeding, as well as smaller thrombi, than dose-adjusted intravenous unfractionated heparin. 23 The use of up-front direct oral anticoagulant agents (factor II and X inhibitors) is also appropriate for patients with lower-risk pulmonary embolism.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…This needs to be further investigated in larger studies, as the LMWH subgroup reported here might have been too small to detect rare complications. In a study evaluating the ability to reach therapeutic partial thromboplastin time with unfractionated heparin infusion in 505 patients with acute PE, 60.6% of patients were subtherapeutic 48 hours after initiation of therapy, 11% were supratherapeutic, and only 28.4% were within therapeutic range (60-80 seconds) (19). Prucnal et al (19) also postulate that treatment with heparin infusion is often justified by the potential need for advanced treatment (ie, endovascular intervention).…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating the ability to reach therapeutic partial thromboplastin time with unfractionated heparin infusion in 505 patients with acute PE, 60.6% of patients were subtherapeutic 48 hours after initiation of therapy, 11% were supratherapeutic, and only 28.4% were within therapeutic range (60-80 seconds) (19). Prucnal et al (19) also postulate that treatment with heparin infusion is often justified by the potential need for advanced treatment (ie, endovascular intervention). Overall, LMWH and heparin at a full therapeutic dose appear to be safe during CDT, although it is not currently endorsed by the Society of Interventional Radiology (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Therapeutische Antikoagulation von Patienten mit Lungenembolie 1. oder UFH oder Fondaparinux 2. Dabigatran 110 mg 2-mal täglich bei Alter ≥ 80 Jahre oder gleichzeitiger Behandlung mit Verapamil 3.…”
unclassified